Catalyst for catalyzing diethylene glycol to prepare N-methylmorpholine and preparation method thereof

By using a catalyst with uniformly distributed Ni, Cu particles and NiCuXY oxide solid solution support, the selectivity and cost control problems of catalyzed diethylene glycol in the prior art are solved, and high efficiency and low energy consumption are achieved Catalytic reaction, suitable for industrial production.

CN119236942APending Publication Date: 2025-01-03BEIJING CTA TEX CHEM
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411340409.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art has shortcomings in the selectivity and production cost control of catalytic diethylene glycol for the preparation of N-methylmorpholine, especially the problem of difficult reactions under high pressure conditions and excessive by-products.

Method used

The catalyst consisting of uniformly distributed Ni, Cu particles and NiCuXY oxide solid solution support was prepared by calcining reduction in hydrogen atmosphere. The interface synergistic effect of the NiCu metal active center and NiCuXY solid solution support was carried out to perform diethylene glycol and acetal. amine reaction.

Benefits of technology

It achieves high N-methylmorpholine selectivity and low cost production, mild reaction conditions and low energy consumption, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236942A_ABST
    Figure CN119236942A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for catalyzing diethylene glycol to prepare N-methylmorpholine and a preparation method of the catalyst, and belongs to the field of catalysts. The catalyst for catalyzing diethylene glycol to prepare N-methylmorpholine is composed of uniformly distributed Ni and Cu particles and a NiCuXY oxide solid solution carrier, and the catalyst is prepared by roasting and reducing a NiCuXY mixed hydroxide precursor in a hydrogen atmosphere; wherein X and Y are selected from any one of Al, Zr, Ce, Cr, Ti, Mo and Mg; and X and Y are different. According to the invention, the interface synergistic effect of a NiCu metal active center and a NiCuXY solid solution carrier is utilized; the catalyst disclosed by the invention is simple in preparation method, relatively low in cost, mild in reaction condition, low in energy consumption and beneficial to being applied to an industrial production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, and in particular to a catalyst for preparing N-methylmorpholine from diethylene glycol and a preparation method thereof. Background Art

[0002] New solvent-processed cellulose fiber, namely Lyocell fiber, uses natural plant fiber as raw material. There is no chemical reaction in the production process. The NMMO solvent used is non-toxic. It is known as the most valuable product in the history of artificial fibers in the past half century. NMMO is the spinning solvent of Lyocell (commonly known as Tencel) and Newcell artificial fiber filaments, which are currently known as "green fibers". It is a solvent that can overcome the extremely strong hydrogen bonds formed by alcohol hydroxyl groups between cellulose molecules in industrial production and can physically dissolve cellulose. NMMO solvent is an indispensable core production factor in the production of Lyocell fiber.

[0003] At present, most of the companies producing NMMO in the world use diethylene glycol as the starting material to synthesize morpholine, then methylate it to synthesize methylmorpholine, and finally oxidize it to synthesize NMMO. Because diethylene glycol is a byproduct of the synthesis of ethylene glycol from ethylene oxide, it is cheap and has sufficient output. The synthesis technology of methylmorpholine is the key to determining the production cost of NMMO. The most research is on the selection of morpholine as the starting material to synthesize N-methylmorpholine, which is also the main method for synthesizing N-methylmorpholine in industry. Because morpholine contains secondary amine groups, it is easy to undergo substitution reactions on the N atom. Different methylation reagents are directly used for N-methylation reactions to generate N-methylmorpholine. However, due to the large fluctuations in the market price of morpholine, it is difficult to control the production cost of synthesizing N-methylmorpholine using morpholine as the starting material.

[0004] The N-alkylation reaction of amines is a reaction between alcohols and alkylamines in a hydrogen environment with the help of a catalyst. This reaction has been studied for decades. In order to reduce the production cost of N-methylmorpholine, BASF once developed a technology for synthesizing N-methylmorpholine in a single step using diethylene glycol and methylamine with the help of a catalyst. However, the industrialization of this technology was eventually abandoned due to the difficulty in controlling the reaction and the excessive number of by-products. Patent CN1083837C discloses a mixture of silicates containing copper or copper oxide and magnesium, and a catalyst containing BaO, Cr2O3 and / or ZnO, which is used to catalyze the reaction of diethylene glycol and methylamine to prepare N-methylmorpholine with a selectivity of 77%. The selectivity of this reaction needs to be improved. The Sichuan Institute of Fine Chemicals was the first in China to propose the use of one or more of the metals such as vanadium, chromium, iron, cobalt, nickel, copper, palladium and platinum, including one or more metal oxides or carbonates, with a ratio of methylamine to diethylene glycol of 1 to 3:1, a reaction temperature of 200-250°C, 1-10Mpa, and the reaction product is separated by distillation to obtain a finished product with a yield of up to 90%. It is estimated that for every ton of N-methylmorpholine produced, about 2 tons of diethylene glycol and 0.8 tons of methylamine are consumed. However, this reaction requires a relatively high pressure and has a relatively high cost for industrial realization. Subsequently, patent CN1911919A proposed a method for simultaneously co-producing N-methylmorpholine and morpholine using diethylene glycol, liquid ammonia and methylamine as raw materials, using Al2O3 and MgO as carriers, and loading a catalyst composed of active components such as nickel and copper, using a fixed bed reactor, a reaction pressure of 1-2.5 MPa, a reaction temperature of 190-260°C, a diethylene glycol flow rate of 0.08-0.2 L / h, a hydrogen to diethylene glycol molar ratio of 20-80:1, and a liquid ammonia to diethylene glycol molar ratio of 5-10: 1. The molar ratio of methylamine to diethylene glycol is 0-3:1, and the gas-solid phase reaction is carried out. The total yield of N-methylmorpholine and morpholine is greater than 85%. The selectivity of N-methylmorpholine in this patent is not high, and further distillation separation is required later. Patent CN111111670A proposes a supported catalyst, which is supported by at least two of alumina, silicon dioxide, titanium dioxide and rare earth molecular sieves, and the oxide catalyst is supported. The yield of N-methylmorpholine obtained by catalyzing the reaction of diethylene glycol and methylamine under hydrogen conditions is 95%. This method has a high yield, but the catalyst preparation process is complicated. Summary of the invention

[0005] The purpose of the present invention is to provide a catalyst for preparing N-methylmorpholine from diethylene glycol and a preparation method thereof.

[0006] Firstly, the present invention provides a catalyst for catalyzing diethylene glycol to prepare N-methylmorpholine, which is composed of uniformly distributed Ni and Cu particles and a NiCuXY oxide solid solution carrier. The catalyst is prepared by calcining and reducing a NiCuXY mixed hydroxide precursor in a hydrogen atmosphere; wherein X and Y are both selected from any one of Al, Zr, Ce, Cr, Ti, Mo and Mg; and X and Y are different.

[0007] More specifically, the X is Al; and the Y is Zr, Ce or Cr.

[0008] In the above catalyst, based on the total mass of the catalyst, the content of Ni particles is 1wt.%~20wt.%, and the content of Cu particles is 1wt.%~20wt.%.

[0009] The present invention further provides a method for preparing the catalyst, comprising the following steps: using NiCuXY mixed hydroxide as a precursor and calcining in a hydrogen atmosphere to obtain the catalyst.

[0010] In the above preparation method, the calcination temperature is 400-550°C and the calcination time is 30 min-300 min.

[0011] In the above-mentioned preparation method, the preparation method of the NiCuXY mixed hydroxide adopts a co-precipitation dynamic crystallization method or a co-precipitation static crystallization method.

[0012] In the above-mentioned preparation method, the preparation of the NiCuXY mixed hydroxide comprises the following steps: dissolving Ni salt, Cu salt, X salt and Y salt in water to obtain solution A; dividing the solution A into two parts, dripping one part of solution A and an ammonia solution into the other part of solution A respectively and controlling the end point pH of the solution to be constant at 9-12, crystallizing, and drying the obtained solid to obtain the NiCuXY mixed hydroxide.

[0013] In the above preparation method, the Ni salt is nickel nitrate; The Cu salt is copper nitrate; The X salt is a nitrate of Al, Zr, Ce, Cr, Ti, Mo or Mg; The Y salt is a nitrate of Al, Zr, Ce, Cr, Ti, Mo or Mg; X and Y are different elements; The molar ratio of the Ni salt, Cu salt, X salt and Y salt is 1: 0.8-1.2:0.8-1.2:0.1-0.5; specifically 1:1:1:0.2; The mass percentage concentration of the Ni salt in solution A is 1% to 20%, specifically 1% to 5%; The mass percentage concentration of the ammonia solution is 0.4% to 1.2%, specifically 1%; The molar number of ammonia in the aqueous ammonia solution is 1 to 3 times the molar number of the divalent ions of the metal salt in the solution A; The crystallization temperature is 60-75° C. and the crystallization time is 6-8 hours, specifically 8 hours.

[0014] In the above preparation method, the X salt is a nitrate of Al; and the Y salt is a nitrate of Zr, Ce or Cr.

[0015] In the above preparation method, at 65-75° C., one portion of solution A and an ammonia solution are respectively dripped into another portion of solution A and the end point pH of the solution is controlled to be constant at 9-12; The pH value of the solution was controlled by adjusting the addition rate of solution A and solution B.

[0016] In the above preparation method, the drying temperature is 65-75°C, specifically 65°C; the drying time is 12-24h, specifically 24h; Before the solid is dried, there is a step of washing the solid; specifically, the washing is carried out using deionized water and ethanol in sequence.

[0017] The invention also provides application of the catalyst in catalyzing diethylene glycol to prepare N-methylmorpholine.

[0018] Finally, the present invention provides a method for preparing N-methylmorpholine, comprising the following steps: mixing diethylene glycol, a methylamine aqueous solution and the above catalyst for reaction to obtain the N-methylmorpholine.

[0019] In the above method, the reaction temperature is 100-300°C; specifically, it can be 180°C; The reaction time is 1 to 6 hours; The reaction pressure is 1-5 MPa; specifically, it can be 0.85 MPa; The molar ratio of diethylene glycol to methylamine is 1:1-6, specifically 1:1.

[0020] In the above method, the mass percentage concentration of the methylamine aqueous solution is 33% to 36%, specifically 36%.

[0021] In the present invention, the interface interaction between Ni and Cu metal particles and the carrier is adjustable, and the interface acid strength is adjustable, thereby obtaining catalysts with different catalytic properties; the above-mentioned adjustability can be obtained through different preparation methods of catalyst precursors.

[0022] The present invention has the following beneficial effects: (1) The catalyst of the present invention is composed of uniformly dispersed metal nanoparticles Ni and Cu and a carrier NiCuXY (X / Y = Al, Zr, Ce, Cr, Ti, Mo, Mg) solid solution; the interface synergy between the NiCu metal active center and the NiCuXY (X / Y = Al, Zr, Ce, Cr, Ti, Mo, Mg) solid solution carrier is utilized; (2) The catalyst preparation method of the present invention is simple, low in cost, mild in reaction conditions, and low in energy consumption, which is conducive to application in industrial production processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the XRD pattern of the catalyst precursor; in the figure, a is NiCuAlZr-OH powder, b is NiCuAlCr-OH powder, and c is NiCuAlCe-OH powder. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, rather than for limiting the scope of the present invention.

[0025] The experimental methods in the following examples are all conventional methods unless otherwise specified.

[0026] The quantitative tests in the following examples were all repeated three times, and the results were averaged.

[0027] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0028] Example 1 Step A: Dynamic coprecipitation crystallization, accurately weigh a certain amount of 0.01mol Ni(NO3)2·6H2O (M = 290.785), 0.01mol Cu(NO3)2·3H2O (M = 241.56), 0.01mol Al(NO3)3·9H2O (M = 375.13), 0.002mol Zr(NO3)4·5H2O (M = 429.32) and dissolve them in 200mL deionized water, stir until completely dissolved to form a transparent salt solution (solution A); 100mL of ammonia solution with a mass percentage concentration of 1% is used as solution B. . At 65°C, solution A (150 mL) and solution B (100 mL) were dripped into a four-necked flask containing 50 mL of solution A using a dropping funnel, and the end point pH value was controlled to be constant at 9-12 (10 in this embodiment); the pH value of the solution was controlled by adjusting the addition rate of solution A and B. After solution A was completely dripped, it was slowly stirred and crystallized in a constant temperature 70°C oil bath for 8 hours. The sample was obtained by suction filtration, washed repeatedly with deionized water 3 times, and finally washed once with anhydrous ethanol, and then the sample was dried in a 65°C oven for 24 hours, ground to obtain NiCuAlZr-OH powder, and dried for storage.

[0029] Step B: The catalytic performance evaluation of the NiCu metal catalyst is carried out on a micro-tubular catalyst evaluation device. Weigh 10g of NiCu metal catalyst precursor (i.e., NiCuAlZr-OH powder) and load it into a reaction tube. First, the catalyst is reduced in situ online, and the reducing gas H2 is introduced to reduce and prepare the catalyst (the reduction temperature is 450°C and the time is 3h). After the reduction is completed, when the temperature drops to the catalytic reaction temperature of 180°C, the liquid feed pump is turned on to introduce the mixed diethylene glycol and 36wt% methylamine aqueous solution, wherein the molar ratio of diethylene glycol to methylamine is 1:1, and the pressure is 0.85Mpa, and then the catalytic reaction is evaluated. The catalytic reaction time is 3h. Using online gas chromatography analysis, the diethylene glycol conversion rate reached 63% and the methylmorpholine selectivity reached 29%.

[0030] Example 2 Step A: Dynamic coprecipitation crystallization, accurately weigh a certain amount of 0.01mol Ni(NO3)2·6H2O (M = 290.785), 0.01mol Cu(NO3)2·3H2O (M = 241.56), 0.01mol Al(NO3)3·9H2O (M = 375.13), 0.002mol Cr(NO3)3·9H2O (M = 400.13) and dissolve them in 200mL of deionized water, stir until completely dissolved, and form a transparent salt solution (solution A); 100mL of ammonia solution with a mass percentage concentration of 1% is used as solution B. At a temperature of 65°C, alkaline solution A (150mL) and solution B (100mL) are respectively dripped into a four-necked flask containing 50mL of solution A with a dropping funnel, and the endpoint pH value is controlled to be constant at 9.5 by adjusting the addition rate of solutions A and B. After solution A was completely dripped, it was crystallized for 8 h under slow stirring in a constant temperature oil bath at 70 °C. The sample was filtered and washed repeatedly with deionized water for 3 times, and finally washed once with anhydrous ethanol, and then dried in an oven at 65 °C for 24 h, ground to obtain NiCuAlCr-OH powder, and stored dry.

[0031] Step B: The catalytic performance evaluation of the NiCu metal catalyst is carried out on a micro-tubular catalyst evaluation device. Weigh 10g of NiCu metal catalyst precursor (NiCuAlCr-OH powder) and load it into the reaction tube. First, the catalyst is reduced in situ online, and the reducing gas H2 is introduced to reduce the catalyst (the reduction temperature is 450°C and the time is 3h). After the reduction is completed, when the temperature drops to the catalytic reaction temperature of 180°C, the liquid feed pump is turned on to introduce the mixed diethylene glycol and 36wt% methylamine aqueous solution, wherein the molar ratio of diethylene glycol to methylamine is 1:1, and the pressure is 0.85Mpa, and then the catalytic reaction is evaluated. The catalytic reaction time is 3h, and the online gas chromatography analysis shows that the diethylene glycol conversion rate reaches 90% and the methylmorpholine selectivity reaches 59%.

[0032] Example 3 Step A: Dynamic coprecipitation crystallization, accurately weigh a certain amount of 0.01mol Ni(NO3)2·6H2O (M = 290.785), 0.01mol Cu(NO3)2·3H2O (M = 241.56), 0.01mol Al(NO3)3·9H2O (M = 375.13), 0.002mol Ce(NO3)3·6H2O (M = 434.22) and dissolve them in 200mL deionized water, stirring until they are completely dissolved to form a transparent salt solution (solution A); 100mL of ammonia solution with a mass percentage concentration of 1% is used as solution B. At 65°C, solution A (150mL) and solution B (100mL) are respectively dripped into a four-necked flask containing 50mL of solution A with a dropping funnel, and the endpoint pH value is controlled to be constant at 10 by adjusting the addition rate of solution A and solution B. After solution A was completely dripped, it was crystallized for 8 h under slow stirring in a constant temperature oil bath at 70 ° C. The sample was filtered and washed repeatedly with deionized water for 3 times, and finally washed once with anhydrous ethanol, and then the sample was dried in an oven at 65 ° C for 24 h, ground to obtain NiCuAlCe-OH powder, and dried and stored.

[0033] Step B: The catalytic performance evaluation of the NiCu metal catalyst is carried out on a micro-tubular catalyst evaluation device. Weigh 10g of NiCu metal catalyst precursor (NiCuAlCe-OH powder) and load it into a reaction tube. First, the catalyst is reduced in situ online, and the reducing gas H2 is introduced to reduce the catalyst (the reduction temperature is 450°C and the time is 3h). After the reduction is completed, when the temperature drops to the catalytic reaction temperature of 180°C, the liquid feed pump is turned on to introduce the mixed diethylene glycol and 36wt% methylamine aqueous solution, wherein the molar ratio of diethylene glycol to methylamine is 1:1, and the pressure is 0.85Mpa, and then the catalytic reaction is evaluated. The catalytic reaction time is 3h. Using online gas chromatography analysis, the diethylene glycol conversion rate reached 91% and the methylmorpholine selectivity reached 90%.

Claims

1. A catalyst for catalyzing diethylene glycol to prepare N-methylmorpholine, which is composed of uniformly distributed Ni and Cu particles and a NiCuXY oxide solid solution carrier, and the catalyst is prepared by calcining and reducing a NiCuXY mixed hydroxide precursor in a hydrogen atmosphere; wherein X and Y are both selected from any one of Al, Zr, Ce, Cr, Ti, Mo and Mg; and X and Y are different.

2. The catalyst according to claim 1, characterized in that: Based on the total mass of the catalyst, the content of Ni particles is 1wt.%~20wt.%, and the content of Cu particles is 1wt.%~20wt.%.

3. The method for preparing the catalyst according to claim 1 or 2, comprising the following steps: using NiCuXY mixed hydroxide as a precursor and calcining in a hydrogen atmosphere to obtain the catalyst.

4. The preparation method according to claim 3, characterized in that: The calcination temperature is 400-550° C., and the calcination time is 30 min-300 min.

5. The preparation method according to claim 3 or 4, characterized in that: The preparation method of the NiCuXY mixed hydroxide adopts a coprecipitation dynamic crystallization method or a coprecipitation static crystallization method.

6. The preparation method according to claim 3 or 4, characterized in that: The preparation of the NiCuXY mixed hydroxide comprises the following steps: dissolving Ni salt, Cu salt, X salt and Y salt in water to obtain solution A; dividing the solution A into two parts, dripping one part of the solution A and an ammonia solution into the other part of the solution A respectively and controlling the end point pH of the solution to be constant at 9-12, crystallizing, and drying the obtained solid to obtain the NiCuXY mixed hydroxide.

7. The preparation method according to claim 8, characterized in that: The Ni salt is nickel nitrate; The Cu salt is copper nitrate; The X salt is a nitrate of Al, Zr, Ce, Cr, Ti, Mo or Mg; The Y salt is a nitrate of Al, Zr, Ce, Cr, Ti, Mo or Mg; X and Y are different elements; The molar ratio of the Ni salt, the Cu salt, the X salt and the Y salt is 1: 0.8-1.2: 0.8-1.2: 0.1-0.5; The mass percentage concentration of the Ni salt in solution A is 1% to 20%; The mass percentage concentration of the ammonia solution is 0.4% to 1.2%; The molar number of ammonia in the aqueous ammonia solution is 1 to 3 times the molar number of the divalent ions of the metal salt in the solution A; The crystallization temperature is 60-75° C. and the crystallization time is 6-8 hours.

8. Use of the catalyst according to claim 1 or 2 in catalyzing the preparation of N-methylmorpholine from diethylene glycol.

9. A method for preparing N-methylmorpholine, comprising the steps of: mixing diethylene glycol, a methylamine aqueous solution and the catalyst according to claim 1 or 2 for reaction to obtain the N-methylmorpholine.

10. The method according to claim 9, characterized in that: The reaction temperature is 100-300°C; The reaction time is 1 to 6 hours; The reaction pressure is 1~5Mpa; The molar ratio of diethylene glycol to methylamine is 1:1-6.

Citation Information

Cited By

  • Cesium-based bimetallic catalyst as well as preparation method and application thereof

    CN121314633A